2002
DOI: 10.1002/lsm.10071
|View full text |Cite
|
Sign up to set email alerts
|

Improved microvessel repair: Laser welding with an anti‐thrombotic solder

Abstract: Solders incorporating heparin should provide in situ anti-thrombotic therapy reducing the risk of microvascular thromboses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The ratio of vascular thrombosis reported in free flap surgery varies between 5.1% and 9.9% (11-13), and for the prevention of this complication, in addition to the suggestions of agents such as botulinum toxins, low molecular weight heparins, aspirin, prostaglandins, dextran inhibitors, and other various agents (14)(15)(16)(17)(18)(19)(20)(21)(22), studies on anastomosis have also been carried out (23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of vascular thrombosis reported in free flap surgery varies between 5.1% and 9.9% (11-13), and for the prevention of this complication, in addition to the suggestions of agents such as botulinum toxins, low molecular weight heparins, aspirin, prostaglandins, dextran inhibitors, and other various agents (14)(15)(16)(17)(18)(19)(20)(21)(22), studies on anastomosis have also been carried out (23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the development of albumin-based solution solders allowed higher biocompatibility between its proteinaceous structure and collagen fibers. As its application is possible with different variations in composition, this solder solution is the most common in these procedures The materials referred to above improve the technical parameters and reduce the thermal damage, enabling the achievement of higher weld strength [43,46,72,76]. Menosky et al [45] concluded that the amount and concentration of structural proteins is directly correlated with the bonding strength of the welded repair.…”
Section: Welding Parameters and Bonding Conditionsmentioning
confidence: 99%
“…Moreover, the development of albumin-based solution solders allowed higher biocompatibility between its proteinaceous structure and collagen fibers. As its application is possible with different variations in composition, this solder solution is the most common in these procedures [40,46,72,76]. For example, BioGlue, which is composed of 45% bovine serum albumin and 10% glutaraldehyde, cross-links with tissue fibers through chemical bindings, allowing vascular chemical stabilization of sutured and welded sites [58].…”
Section: Welding Parameters and Bonding Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in an in vivo setting, genipin has the potential to increase resilience to cell-mediated and enzymatic degradation [111,118]. Future application in the clinical setting should consider employing a concentrated autologous plasma protein [119][120][121]. However, the higher denaturation temperature of HSA might require higher lasing parameters, which increases the risk of inflicting more extensive thermal damage [52].…”
Section: Future Perspectivesmentioning
confidence: 99%